2009
DOI: 10.1016/j.hrthm.2009.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Left versus right atrial difference in dominant frequency, K+ channel transcripts, and fibrosis in patients developing atrial fibrillation after cardiac surgery

Abstract: Background-Atrial fibrillation (AF) developing after cardiac surgery is associated with adverse outcomes; however, the mechanism(s) that trigger and maintain AF in these patients are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 31 publications
16
80
0
Order By: Relevance
“…Recent clinical studies showed that POAF originated from the LA and not from the pulmonary veins (PVs) [36,37] as in the present study. Furthermore it was shown in post-surgical patients manifesting increased atrial tissue fibrosis (confirmed by biopsies) facilitated the emergence LA foci (“sources”) leading to AF [6,25]. That indeed the EAD-mediated triggered activity is the final path to AF initiation is emphasized by suppressing the AF by the selective block of the I Na-L with GS-967 a powerful and selective inhibitor of EADs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies showed that POAF originated from the LA and not from the pulmonary veins (PVs) [36,37] as in the present study. Furthermore it was shown in post-surgical patients manifesting increased atrial tissue fibrosis (confirmed by biopsies) facilitated the emergence LA foci (“sources”) leading to AF [6,25]. That indeed the EAD-mediated triggered activity is the final path to AF initiation is emphasized by suppressing the AF by the selective block of the I Na-L with GS-967 a powerful and selective inhibitor of EADs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased systemic and atrial myocardial oxidative stress is often observed in post-operative patients with new onset (acute) paroxysmal AF (POAF) [3,4] with an incidence of up to 50% [5]. Diverse etiological factors such as fibrosis [6,7] and increased Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) activity [8,9] among others, are thought to play a key role in the initiation of oxidative AF [4,10]. While the causative and signaling factors of oxidative AF are reasonably well identified, the mechanism of spontaneous initiation (i.e., not induced by electrical stimulation) of acute oxidative AF in experimental and human studies, remains undefined [10].…”
Section: Introductionmentioning
confidence: 99%
“…The 2 2DDCt method was used for analysis of gene expression, as described in other studies. 21,22 Briefly, equation DCt was Ct of each target gene transcript 2 Ct of Gapdh, and DDCt was calculated using the following formula: DDCt 5 DCt [target gene in experiment group] 2 DCt [target gene in control group], then the relative fold difference was calculated using the formula 2 2DDCt .…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…Recently, we reported the signi cance of sympathetic nervous system abnormality for predicting perpetuated AF in patients with paroxysmal AF 23 , and the magnitude of nerve sprouting and hyperinnervation has been reported to be higher in the RA than in the LA in a canine model of AF produced by prolonged RA pacing, further suggesting the signi cance of RA 24 . The percentage area occupied by brosis was also recently shown to be higher in the LA than in the RA of patients who developed AF, suggesting more reversible and quick changes to the right atrium 25 . Our result thus con rms that RA volume is important for morbidity in patients with AF.…”
Section: Discussionmentioning
confidence: 91%